A medium temperature curing epoxy resin composition, prepreg and method of manufacture
Patent Information
- Application Number
- CN202611461558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
但是,该现有技术的环氧树脂基体层本身仍含有一定量的核壳结构聚合物粒子,功能化增韧层则需要另外制备包含增韧剂、表面改性纳米黏土和热塑性树脂超细颗粒的浆料
(1)本发明通过反应型增韧剂A、颗粒型增韧剂B和不溶性热塑性增韧剂C的三元协同复配,三种增韧剂分别在裂纹萌生、基体裂纹扩展和层间损伤扩展等不同阶段发挥互补作用,在显著提高复合材料冲击后压缩强度的同时,还能保持或提高其0°压缩强度。 由实施例1和对比例1可知,本发明实施例1的0°压缩强度达1452MPa、CAI达210.6MPa,较仅采用增韧剂A增韧的对比例1(0°压缩强度1315MPa、CAI 157.2MPa)分别提高了约10.4%和34.0%,克服了现有技术中增韧与刚度和强度难以兼顾的技术难题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of fiber-reinforced resin-based composite materials, and specifically relates to a medium-temperature curing epoxy resin composition, prepreg, and preparation method. Background Technology
[0002] Epoxy resin-based carbon fiber composites have the characteristics of high specific strength, high specific modulus, good fatigue resistance and strong structural designability. They are widely used in aerospace, rail transportation, wind power equipment and high-end electronic packaging, and are especially suitable for components with high requirements for lightweight structure and load-bearing capacity.
[0003] However, after curing, epoxy resin typically forms a three-dimensional network structure with a high cross-linking density, resulting in relatively limited plastic deformation capacity and crack propagation resistance. When epoxy resin composites are subjected to impact loads, they are prone to damage such as matrix cracking, fiber / resin interface debonding, and interlaminar delamination. This leads to a significant reduction in the stable load-bearing capacity of the laminate under subsequent compressive loads, manifested as a decrease in post-impact compressive strength (CAI), thus limiting the application of this type of material in impact-resistant structural components.
[0004] To improve the toughness of epoxy resins and their composites, rubber elastomers, core-shell polymer particles, thermoplastic resins, or inorganic nanomaterials are typically introduced into the epoxy resin. Different types of toughening components can inhibit crack initiation and propagation through mechanisms such as particle cavitation, matrix shear yielding, crack deflection, crack pinning, interfacial debonding energy dissipation, or thermoplastic phase bridging, thereby improving the fracture toughness and impact damage tolerance of the material. However, a single toughening component usually cannot simultaneously achieve the desired effects on the resin's bulk toughness, interlaminar toughness, heat resistance, stiffness, strength, and prepreg processing properties. For example, while increasing the amount of rubber or thermoplastic resin can improve the deformation capacity of epoxy resin, it can also cause an increase in system viscosity, a decrease in glass transition temperature and resin modulus, affecting the resin's wetting properties and processing properties. Inorganic nanomaterials, although helpful in improving stiffness and inhibiting crack propagation, their dispersion state and interfacial compatibility can significantly affect the toughening effect, and insufficient dispersion may also lead to local defects or stress concentration. Ultimately, the flexural strength and compressive strength of the finished product cannot be improved in tandem with the post-impact compressive strength and interlaminar shear strength. This is especially true in widely used and cost-sensitive medium-temperature curing epoxy resin systems, where a balance must be struck between material cost and overall performance.
[0005] Patent application CN122145975A discloses a high-toughness, high-temperature epoxy prepreg that cures at 180°C. This prepreg employs a layered structure, comprising, from the inside out, a fiber reinforcement layer, an epoxy resin matrix layer, and a functionalized toughening layer. The epoxy resin matrix layer contains liquid epoxy resin, solid epoxy resin, and core-shell polymer particles with a polybutadiene rubber core and a polymethyl methacrylate shell. The functionalized toughening layer contains epoxy resin, another toughening agent, surface-modified nanoclay, and ultrafine thermoplastic resin particles. This patent application proposes a layered toughening technique for prepregs by setting an epoxy resin matrix layer and a functionalized toughening layer, and configuring core-shell rubber particles, surface-modified nanoclay, and ultrafine thermoplastic resin particles in different resin regions. This approach facilitates the concentrated distribution of toughening components in specific regions, reducing the potential for excessively high system viscosity when all toughening materials are uniformly added to the main resin. It also improves interlayer damage tolerance through multiple mechanisms, including particle toughening, nanomaterial crack retardation, and thermoplastic phase toughening. However, the epoxy resin matrix layer in this prior art still contains a certain amount of core-shell polymer particles, and the functionalized toughening layer requires the separate preparation of a slurry containing toughening agents, surface-modified nanoclay, and ultrafine thermoplastic resin particles. Therefore, this approach places certain requirements on the particle size, dispersion state, interlayer distribution, and rheological properties of different toughening components. Its toughening effect may be influenced by the thickness and uniformity of the functionalized toughening layer, the degree of nanomaterial dispersion, and the morphology of the thermoplastic particles. Furthermore, this existing technology mainly constructs granular and interlayer toughening structures using core-shell rubber particles, nano-clay, and thermoplastic ultrafine particles. Its toughening mechanism focuses on physically hindering crack propagation and interlayer delamination. However, there is still room for further research and optimization regarding how to utilize toughening components that can participate in the curing reaction or regulate the curing network structure to improve the plastic deformation capacity of the matrix while maintaining the heat resistance, stiffness, and compressive load-bearing capacity of the crosslinked network, as well as how to coordinate the effects of different toughening components within the matrix and in the interlayer region.
[0006] Therefore, there is a need to provide a synergistic toughening system and prepreg suitable for medium-temperature epoxy resin-based carbon fiber composites. By using toughening components with different mechanisms of action and spatial scales, the curing network, matrix crack propagation, and interlaminar delamination behavior can be controlled respectively. Under the condition of not changing the resin's medium-temperature curing regime of 125°C, the interlaminar toughness and impact damage tolerance of the composite material can be improved, while maintaining or improving its heat resistance, 0° compressive strength, and post-impact compressive strength. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing medium-temperature epoxy resin toughening systems in the prior art, which are unable to simultaneously improve the 0° compressive strength and post-impact compressive strength of carbon fiber composites, and to provide a medium-temperature curing epoxy resin composition, prepreg, and preparation method.
[0008] In a first aspect, the present invention provides a medium-temperature curing epoxy resin composition comprising the following raw materials in parts by weight:
[0009] Epoxy resin: 100 parts; Hardener: 2-4 parts; Accelerator: 0.5-2 parts; And composite toughening agents; The composite toughening agent includes A: reactive toughening agent, B: particulate toughening agent and C: insoluble thermoplastic toughening agent; The weight parts of A are 12-16, the weight parts of B are 2-4, and the weight parts of C are 8-14.
[0010] Preferably, the epoxy resin comprises phenolic epoxy resin, multifunctional epoxy resin, and bisphenol A epoxy resin; Based on a total epoxy resin weight of 100 parts, the phenolic epoxy resin comprises 10-25 parts, the multifunctional epoxy resin comprises 35-50 parts, and the bisphenol A epoxy resin comprises 40-55 parts.
[0011] Preferably, the curing agent is dicyandiamide and the accelerator is a urea-based accelerator.
[0012] Preferably, the reactive toughening agent is selected from at least one of polyethersulfone, polysulfone, or polyaryletherketone containing a phenolphthalein structure; The granular toughening agent is selected from at least one of powdered rubber, core-shell rubber particles, or nano-silica. The insoluble thermoplastic toughening agent C is selected from at least one of polyphenylene sulfide, polyetheretherketone, polyaryletherketone, or nylon.
[0013] Preferably, the reactive toughening agent A is a polyaryletherketone containing a phenolphthalein structure, the particulate toughening agent B is nano-rubber, and the insoluble thermoplastic toughening agent C is nylon 6.
[0014] Preferably, the weight ratio of A, B and C is: A∶B∶C = 14∶2∶12.
[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned medium-temperature curing epoxy resin composition, specifically comprising the following steps: Step 1: Mix bisphenol A type epoxy resin, multifunctional epoxy resin and reactive toughening agent A evenly, and stir at 100℃-120℃ for 90-120 minutes until the blend becomes transparent. Step 2: Cool down to 80℃-90℃, add phenolic epoxy resin and granular toughening agent B, and stir evenly; Step 3: Cool down to 70℃-80℃, add insoluble thermoplastic toughening agent C and curing agent, and stir evenly; Step 4: Cool down to 60℃-70℃, add the accelerator, and stir well; Step 5: Grind the mixture obtained in Step 4 to obtain the medium-temperature curing epoxy resin composition.
[0016] Preferably, in step five, a three-roll mill is used for grinding, and the grinding is performed 3-5 times.
[0017] Preferably, in step one, the temperature for heat preservation and stirring is 110°C, and the time is 120 min.
[0018] Thirdly, the present invention provides a prepreg comprising reinforcing fibers and the above-described medium-temperature curing epoxy resin composition, wherein the medium-temperature curing epoxy resin composition is impregnated in the reinforcing fibers.
[0019] Preferably, the reinforcing fiber is carbon fiber.
[0020] Preferably, the prepreg has a fiber areal density of 133 g / m² and a resin content of 33 wt%.
[0021] Fourthly, a method for preparing a prepreg includes the following steps: The above-mentioned medium-temperature curing epoxy resin composition is made into a film; The prepreg is prepared by impregnating reinforcing fibers with the aforementioned adhesive film.
[0022] Preferably, the method further includes the following steps: The prepreg is laid to obtain a prepreg layup; The prepreg layup is placed in an autoclave, a pressure of 0.6-0.7 MPa is applied, and the temperature is raised to 125°C at a rate of 1-3°C / min. The temperature is maintained and cured for 2 hours, and then the temperature is lowered to below 60°C to obtain a composite material laminate.
[0023] Preferably, after curing the composition at 125°C for 2 hours, the glass transition temperature of the casting is ≥138°C, the 0° compressive strength of the carbon fiber composite material is ≥1423MPa, and the post-impact compressive strength is ≥178.5MPa.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention utilizes a ternary synergistic compound of reactive toughening agent A, particulate toughening agent B, and insoluble thermoplastic toughening agent C. The three toughening agents play complementary roles at different stages, such as crack initiation, matrix crack propagation, and interlaminar damage propagation. This significantly improves the post-impact compressive strength of the composite material while maintaining or increasing its 0° compressive strength. As shown in Example 1 and Comparative Example 1, the 0° compressive strength of Example 1 of this invention reaches 1452 MPa and CAI reaches 210.6 MPa, which are approximately 10.4% and 34.0% higher than those of Comparative Example 1 (0° compressive strength 1315 MPa and CAI 157.2 MPa) toughened only by toughening agent A. This overcomes the technical difficulty in balancing toughening with stiffness and strength in the prior art.
[0025] (2) While introducing toughening agents to improve the toughness of the material, the present invention can still maintain high heat resistance. As can be seen from Example 1 and Comparative Example 1, the glass transition temperature of Example 1 of the present invention is 143.36℃, which is only 1.54℃ lower than that of Comparative Example 1 (Tg 144.90℃) toughened only by toughening agent A. The glass transition temperature is not lower than 138℃, which meets the requirements for use of medium-temperature curing epoxy resin in high-temperature environments.
[0026] (3) By regulating the cured network structure through reactive toughening agent A, the present invention effectively improves the interfacial compatibility between particulate toughening agent B and insoluble thermoplastic toughening agent C and epoxy resin matrix, avoiding a significant decrease in heat resistance and rigidity caused by the introduction of rubber phase or thermoplastic phase, thereby making the composition have both good toughness, heat resistance and rigidity.
[0027] (4) The preparation method provided by the present invention adopts the step-by-step feeding and gradual cooling method, combined with three-roll milling and dispersion, so that each toughening component forms its own suitable dispersion state and phase structure in the matrix, which is highly operable; the curing temperature of the composition is 125℃, which belongs to the medium temperature curing system, and is compatible with the existing medium temperature curing prepreg production process equipment. It does not require major modification of the existing production line and has good industrial promotion value. Detailed Implementation
[0028] The present invention will now be described in further detail with reference to specific embodiments. However, this should not be construed as limiting the scope of the present invention to the following embodiments; all technologies implemented based on the content of the present invention fall within the scope of the present invention.
[0029] 1. Raw Material Description Unless otherwise stated, the amounts of each component in the following examples and comparative examples are in parts by weight.
[0030] The main raw materials used in this specific embodiment are as follows, but are not limited to the following list: (a) Epoxy resin Phenolic epoxy resin: selected from F-51 (Korea Gukdo Chemical), F-44 (Korea Gukdo Chemical) or TSQCN700 (Shandong Shengquan) series, epoxy equivalent 190-205g / eq; Multifunctional epoxy resins: Tetrafunctional epoxy TGDDM is selected from AG-80 (Nantong Qianyi), AG80 (Shanghai Huayi Resin), and TT-410 (Tiantai Chemical); trifunctional epoxy is selected from AFG-90 (Shanghai Huayi Resin), TT-300 (Tiantai Chemical), or S510 (Nantong Xinnaxi); triglycidyl p-aminophenol. Epoxy equivalent 93-106 g / eq.
[0031] Bisphenol A type epoxy resin: selected from E-51 (Nantong Xingchen Synthetic Materials), EPON 828 (Hansen Chemical) or E-54 (Nantong Xingchen Synthetic Materials), with an epoxy equivalent of approximately 184-194 g / eq.
[0032] (ii) Curing agents and accelerators Latent curing agent: dicyandiamide, selected from Dyhard 100S (Degussa) or Dycure 6S (Ningxia Hengkang). Urea accelerators: selected from UR-300 (Sanhe Chemical), 100B-U (Guangdong Guoyan Electronic Materials) or UR500 (Hubei Xinkang Pharmaceutical Chemical).
[0033] (III) Composite toughening agent Reactive toughening agent A: Polyaryletherketone (PEK-C) containing phenolphthalein structure, purchased from Xuzhou Engineering Plastics Factory, Tsinghua Jiguang or Hanshuo High-tech, with a number average molecular weight of about 30,000-50,000, has phenolphthalein side groups and hydroxyl end groups, and can participate in epoxy curing reaction.
[0034] Granular toughening agent B: Selected from nano-powder carboxyl rubber VP-5011 (Kunlun Petrochemical), 2097 (Lanzhou Petrochemical), or core-shell rubber particles MX-154 (Kanebuchi, Japan), the number of which is calculated based on the actual mass of toughening particles contained. Insoluble thermoplastic toughening agent C: Nylon 6 (PA6), selected from ultrafine powder or film-grade chips of Tsinghua Jiguang and Akema, with a particle size of about 20-80μm, maintains an independent phase structure during epoxy curing.
[0035] Example 1 Preparation of epoxy resin compositions This embodiment provides a medium-temperature curing epoxy resin composition, the formulation of which is shown in Table 1.
[0036] Table 1. Formulation composition of Example 1
[0037] The epoxy resin composition was prepared according to the following steps: Step 1: Add 48 parts by weight of bisphenol A type epoxy resin (E-51), 40 parts by weight of multifunctional epoxy resin (AG-80), and 14 parts by weight of reactive toughening agent A (PEK-C) to the reactor and mix thoroughly. Under stirring conditions, heat to 110°C and maintain the temperature for 120 minutes until the blend becomes transparent and homogeneous.
[0038] Step 2: Cool the reactor to 85℃, and add 12 parts by weight of phenolic epoxy resin (F-51) and 2 parts by weight of granular toughening agent B (nano rubber mother liquor, calculated based on effective nano rubber particles) under stirring. Stir until homogeneous. After the materials are in a uniform state, add the next material.
[0039] Step 3: Cool the reactor to 75°C, add 12 parts by weight of insoluble thermoplastic toughening agent C (PA6) and 4 parts by weight of dicyandiamide curing agent under stirring, and stir evenly.
[0040] Step 4: Cool the reactor to 65°C, add 1.5 parts by weight of urea accelerator (UR-300) under stirring, and stir until homogeneous.
[0041] Step 5: Grind the mixture obtained in Step 4 using a three-roll mill for 4 times to obtain a homogeneous epoxy resin composition.
[0042] Preparation of resin castings The epoxy resin composition obtained in Example 1 was poured into a mold and placed in an oven for curing. The curing process was as follows: the temperature was raised from room temperature to 125°C, and cured at 125°C for 2 hours. Then, the temperature was allowed to drop naturally until the sample temperature dropped below 60°C. The sample was then removed from the mold to obtain the resin casting sample.
[0043] Preparation of prepreg and composite laminate The epoxy resin composition obtained in Example 1 was used to prepare a film by a blade coating method, and the film thickness was controlled to be uniform. This film was then used to impregnate T700 grade carbon fibers (fiber areal density of 133 g / m²), with the resin content controlled at 33 wt%, to obtain a medium-temperature curing epoxy prepreg for carbon fibers.
[0044] Following the specimen dimensions and layup methods specified in ASTM D6641 (0°C compressive strength test), ASTM D7136, and ASTM D7137 (post-impact compressive strength test), the prepreg was cut and laid to obtain a prepreg layup. The layup was placed in an autoclave, and a pressure of 0.6 MPa was applied starting from room temperature. The temperature was increased to 125°C at a rate of 2°C / min. The substrate was then cured at 125°C for 2 hours. After curing, the substrate was cooled to below 60°C at a rate of 3°C / min. The pressure was released, and the substrate was removed to obtain a carbon fiber reinforced epoxy resin composite laminate.
[0045] Example 2 The only difference between this embodiment and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system in this embodiment are exactly the same as those in Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide, and 1.5 parts of urea accelerator.
[0046] In this embodiment, toughening agent A is 12 parts, toughening agent B is 2 parts, and toughening agent C is 14 parts, that is, A:B:C=12:2:14.
[0047] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0048] Example 3 The only difference between this embodiment and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system in this embodiment are exactly the same as those in Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide, and 1.5 parts of urea accelerator.
[0049] In this embodiment, toughening agent A is 16 parts, toughening agent B is 4 parts, and toughening agent C is 8 parts, that is, A∶B∶C=16∶4∶8.
[0050] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0051] Example 4 The only difference between this embodiment and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system in this embodiment are exactly the same as those in Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide, and 1.5 parts of urea accelerator.
[0052] In this embodiment, toughening agent A is 8 parts, toughening agent B is 6 parts, and toughening agent C is 14 parts, that is, A∶B∶C=8∶6∶14.
[0053] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0054] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is the type and amount of toughening agent. The epoxy resin system and curing system of Comparative Example 1 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0055] In Comparative Example 1, toughening agent A was 16 parts, and toughening agents B and C were not added, that is, only toughening agent A was used for toughening.
[0056] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0057] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is the type and amount of toughening agent. The epoxy resin system and curing system of Comparative Example 2 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0058] In Comparative Example 2, toughening agent A was 8 parts, toughening agent B was 4 parts, and toughening agent C was not added, that is, toughening agent A and toughening agent B were used for binary toughening.
[0059] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0060] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is the type and amount of toughening agent. The epoxy resin system and curing system of Comparative Example 3 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0061] In Comparative Example 3, toughening agent A was 8 parts, toughening agent C was 14 parts, and toughening agent B was not added, that is, toughening agent A and toughening agent C were used for binary toughening.
[0062] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0063] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is the type and amount of toughening agent. The epoxy resin system and curing system of Comparative Example 4 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0064] In Comparative Example 4, toughening agent A was not added, toughening agent B was 4 parts, and toughening agent C was 14 parts, that is, only toughening agents B and C were used for binary toughening.
[0065] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0066] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system of Comparative Example 5 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0067] In Comparative Example 5, toughening agent A was 12 parts, toughening agent B was 8 parts (exceeding the upper limit of 2-4 parts specified in this invention), and toughening agent C was 8 parts, i.e. A∶B∶C=12∶8∶8.
[0068] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0069] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system of Comparative Example 6 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0070] In Comparative Example 6, toughening agent A was 18 parts (exceeding the upper limit of 12-16 parts as defined in this invention), toughening agent B was 2 parts, and toughening agent C was 8 parts, i.e., A∶B∶C=18∶2∶8.
[0071] The preparation method is the same as in Example 1.
[0072] Comparative Example 7 The only difference between Comparative Example 7 and Example 1 is the amount of toughening agent used. The epoxy resin system and curing system of Comparative Example 7 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide and 1.5 parts of urea accelerator.
[0073] In Comparative Example 7, toughening agent A was 12 parts, toughening agent B was 2 parts, and toughening agent C was 18 parts (exceeding the upper limit of 8-14 parts specified in this invention), that is, A∶B∶C=12∶2∶18.
[0074] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0075] Comparative Example 8 The only difference between Comparative Example 8 and Example 1 is the type of toughening agent used, while the amount used is the same. The epoxy resin system and curing system of Comparative Example 8 are exactly the same as those of Example 1, namely: 12 parts of phenolic epoxy resin, 40 parts of multifunctional epoxy resin, 48 parts of bisphenol A epoxy resin, 4 parts of dicyandiamide, and 1.5 parts of urea accelerator.
[0076] In Comparative Example 8, toughening agent A consisted of 14 parts PES-C (replacing PEK-C), toughening agent B consisted of 2 parts core-shell rubber (replacing nano rubber), and toughening agent C consisted of 12 parts PA6.
[0077] The preparation methods, resin castings, and composite materials are all the same as in Example 1.
[0078] The toughening agent compositions of each embodiment and comparative example are summarized in Table 2.
[0079] Table 2. Toughening agent composition of each embodiment and comparative example.
[0080] Performance testing methods Glass transition temperature test Following the method specified in ASTM D7028, the resin casting samples prepared in each embodiment and comparative example were tested using a dynamic mechanical analyzer to obtain the glass transition temperature of each resin composition cured product.
[0081] 0° compressive strength test Following the method specified in ASTM D6641, reinforcing sheets were glued onto the composite laminates prepared in each embodiment and comparative example, and 0° compression performance tests were performed to obtain 0° compression strength.
[0082] Post-impact compressive strength (CAI) test Following the methods specified in ASTM D7136 and ASTM D7137, the composite laminates prepared in each embodiment and comparative example were subjected to post-impact compression tests to obtain the post-impact compression strength.
[0083] The performance test results of each embodiment and comparative example are shown in Table 3.
[0084] Table 3 Performance test results of each embodiment and comparative example
[0085] Note: In Comparative Example 6, due to the excessive addition of toughening agent A (PEK-C) (18 parts), the viscosity of the resin system was too high, resulting in extremely poor fluidity during the casting process. Furthermore, it was impossible to prepare prepregs and composite laminates through processes such as coating and impregnation. Therefore, it was impossible to obtain the corresponding mechanical property data and glass transition temperature.
[0086] Results Analysis Comparative Example 1 used only toughening agent A for toughening. Toughening agent A contains reactive groups that can participate in the curing reaction of epoxy resin, introducing corresponding molecular chain segments into the cured crosslinking network, thereby balancing the rigidity and toughness of the resin system to a certain extent. As shown in Table 3, the composite material obtained in Comparative Example 1 has a 0° compressive strength of 1315 MPa and a CAI of 157.2 MPa.
[0087] Comparative Example 2 used 8 parts toughening agent A and 4 parts nano-rubber toughening agent B. Nano-rubber particles can dissipate crack propagation energy through mechanisms such as particle cavitation, plastic deformation, and induced matrix shear yielding, which is beneficial for improving the toughness of the material. However, the increased rubber phase content may affect the epoxy resin curing network structure. The glass transition temperature of Comparative Example 2 was 138.25℃, lower than that of Comparative Example 1 (144.90℃), and its 0° compressive strength was 1181 MPa.
[0088] Comparative Example 3 used 8 parts of toughening agent A and 14 parts of insoluble thermoplastic toughening agent C. The insoluble thermoplastic toughening agent, dispersed in the epoxy resin matrix, can dissipate energy through thermoplastic phase deformation, crack deflection, and bridging. However, when the amount of insoluble thermoplastic toughening agent added is large, the thermoplastic dispersed phase may agglomerate or form large phase regions, resulting in localized stress concentration. The composite material obtained in Comparative Example 3 had a 0° compressive strength of 1264 MPa and a CAI of 155.9 MPa.
[0089] Comparative Example 4 used 4 parts of nano-rubber toughening agent B and 14 parts of insoluble thermoplastic toughening agent C, without adding toughening agent A. Due to the absence of toughening agent A, which can regulate the cured network structure, the compatibility between the nano-rubber particles and the thermoplastic dispersed phase and the epoxy resin matrix was poor, resulting in weak interfacial bonding. Consequently, its 0° compressive strength was only 1127 MPa, and its CAI was only 141.9 MPa, both the lowest among all comparative examples. This indicates that toughening agent A, as a reactive component, not only regulates the network structure by participating in the curing reaction but also plays a crucial role in improving the interfacial compatibility between the particulate toughening agent B and the insoluble thermoplastic toughening agent C and the matrix.
[0090] 2. Analysis of Examples 1-4 Examples 1-4 used a combination of toughening agents A, B, and C. Table 3 shows that the composite materials obtained in Examples 1-4 had a 0° compressive strength of 1423-1452 MPa and a CAI of 178.5-210.6 MPa, both higher than all comparative examples. Examples 1-3 had a 0° compressive strength of 1437-1452 MPa, a CAI of 197.4-210.6 MPa, and a glass transition temperature of 141.87-143.36 °C. Compared to Comparative Example 1, which used only toughening agent A, Examples 1-3 improved the 0° compressive strength and CAI while only decreasing the glass transition temperature by approximately 1.54-3.03 °C.
[0091] Among them, Example 1 exhibits the best overall performance, with a 0° compressive strength of 1452 MPa, a CAI of 210.6 MPa, and a glass transition temperature of 143.36°C. Compared with Comparative Example 1, Example 1 shows an increase of approximately 10.4% in 0° compressive strength, an increase of approximately 34.0% in CAI, and a decrease of only 1.54°C in glass transition temperature.
[0092] In Example 4, toughening agent A was 8 parts (below the lower limit of 12 parts specified in this invention), and toughening agent B was 6 parts (above the upper limit of 4 parts specified in this invention). Although the CAI reached 178.5 MPa, which is still higher than all comparative examples, it was significantly lower than Examples 1-3 (197.4-210.6 MPa), and the glass transition temperature also dropped to 138.08°C. This indicates that even if all three toughening agents are present, the synergistic toughening effect will be weakened if the ratio exceeds the range specified in this invention.
[0093] 3. Analysis of Comparative Examples 5-8 – Criticality of Proportioning Range In Comparative Example 5, the amount of nano-rubber toughening agent B was 8 parts (exceeding the upper limit of 2-4 parts specified in this invention). Due to the excessive amount of nano-rubber, agglomeration occurred in the resin system, forming a rubber phase with uncontrollable particle size and insufficient bonding with the resin interface. Simultaneously, the resin flowability deteriorated, affecting molding quality. The 0° compressive strength of Comparative Example 5 was 1338 MPa, and the CAI was 142.7 MPa, significantly lower than that of Examples 1-3. This indicates that there is an upper limit to the amount of toughening agent B; excessive addition not only fails to further improve toughness but also leads to a decrease in mechanical properties due to agglomeration and interface problems.
[0094] In Comparative Example 6, toughening agent A was 18 parts (exceeding the 12-16 parts upper limit specified in this invention). In step one, toughening agent A forms a preliminary crosslinking network with the epoxy resin prepolymer. Appropriate amounts can improve the film-forming properties and mechanical properties of the resin. However, when the amount added is too large, the crosslinking network becomes excessively dense, the resin hardness and viscosity increase sharply, and the flowability decreases significantly, making it impossible to prepare prepregs through processes such as coating or impregnation. This indicates that there is an upper limit to the amount of toughening agent A; exceeding this limit will render the composition unworkable.
[0095] In Comparative Example 7, the toughening agent C was 18 parts (exceeding the upper limit of 8-14 parts specified in this invention). PA6 achieves toughening through the formation of interpenetrating networks and thermoplastic phase transformation, but when excessive PA6 is added, the originally fine toughening phase interface expands, and cracks can propagate rapidly along the phase interface, resulting in the opposite of the toughening effect. The CAI of Comparative Example 7 decreased to 159.55 MPa, far lower than that of Examples 1-3. This indicates that there is also an upper limit to the amount of toughening agent C used.
[0096] As can be seen from Comparative Examples 5-7, the dosage of all three toughening agents must be within the range specified in this invention to achieve a synergistic toughening effect. Exceeding the upper limit of any component will lead to a significant decrease in 0° compressive strength or CAI, and may even result in the loss of process feasibility.
[0097] 4. Analysis of Comparative Example 8 – Replacement of Toughening Agent Type In Comparative Example 8, toughening agent A was replaced with PES-C, and toughening agent B was replaced with core-shell rubber, with the same dosage as in Example 1. Its 0° compressive strength was 1426 MPa, CAI was 201.2 MPa, and glass transition temperature was 144.64°C. Its overall performance was still superior to all comparative examples with missing components or out-of-range proportions, but slightly lower than that of Example 1. According to known principles in the art, PES-C is slightly less effective than PEK-C in improving resin strength and modulus. This may be because the steric hindrance of sulfone groups is greater than that of carbonyl groups. Introducing sterically hindered sulfone groups into the cured structure will have a certain impact on the density of the cured system, leading to a slight decrease in mechanical properties. However, this result also shows that by replacing toughening agents within the range defined in this invention, composite materials with superior overall performance can still be obtained.
[0098] 5. Summary The above results demonstrate that this invention achieves superior overall performance compared to single-component or binary-component formulations through the synergistic compounding of reactive toughening agent A, particulate toughening agent B, and insoluble thermoplastic toughening agent C. Toughening agent A modulates the epoxy resin curing network structure and improves the interfacial compatibility between toughening agents B and C and the matrix. Toughening agent B dissipates crack propagation energy through cavitation and plastic deformation, while toughening agent C inhibits crack propagation through thermoplastic phase deformation, crack deflection, and bridging. The three toughening agents act on different toughening processes, playing complementary roles at different stages such as crack initiation, matrix crack propagation, and interlaminar damage propagation.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A medium-temperature curing epoxy resin composition, characterized in that, It contains the following ingredients by weight: Epoxy resin: 100 parts; Hardener: 2-4 parts; Accelerator: 0.5-2 parts; And composite toughening agents; The composite toughening agent includes A: reactive toughening agent, B: particulate toughening agent and C: insoluble thermoplastic toughening agent; The weight parts of A are 12-16, the weight parts of B are 2-4, and the weight parts of C are 8-14.
2. The medium-temperature curing epoxy resin composition according to claim 1, characterized in that, The epoxy resin includes phenolic epoxy resin, multifunctional epoxy resin and bisphenol A epoxy resin. Based on a total epoxy resin weight of 100 parts, the phenolic epoxy resin is 10-25 parts, the multifunctional epoxy resin is 35-50 parts, and the bisphenol A epoxy resin is 40-55 parts. The curing agent is dicyandiamide, and the accelerator is a urea-based accelerator.
3. The medium-temperature curing epoxy resin composition according to claim 1, characterized in that, The reactive toughening agent is selected from at least one of polyethersulfone, polysulfone, or polyaryletherketone containing a phenolphthalein structure; The granular toughening agent is selected from at least one of powdered rubber, core-shell rubber particles, or nano-silica. The insoluble thermoplastic toughening agent C is selected from at least one of polyphenylene sulfide, polyetheretherketone, polyaryletherketone, or nylon.
4. The medium-temperature curing epoxy resin composition according to claim 1, characterized in that, The reactive toughening agent is a polyaryletherketone containing a phenolphthalein structure, the particulate toughening agent is nano-rubber, and the insoluble thermoplastic toughening agent is nylon 6; the weight ratio of A, B and C is: A∶B∶C = 14∶2∶12.
5. The method for preparing the medium-temperature curing epoxy resin composition according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Mix bisphenol A type epoxy resin, multifunctional epoxy resin and reactive toughening agent A evenly, and stir at 100℃-120℃ for 90-120 minutes until the blend becomes transparent. Step 2: Cool down to 80℃-90℃, add phenolic epoxy resin and granular toughening agent, and stir evenly; Step 3: Cool down to 70℃-80℃, add insoluble thermoplastic toughening agent and curing agent, and stir evenly; Step 4: Cool down to 60℃-70℃, add the accelerator, and stir well; Step 5: Grind the mixture obtained in Step 4 to obtain the medium-temperature curing epoxy resin composition.
6. The preparation method according to claim 5, characterized in that, In step one, the temperature for heat preservation and stirring is 110℃ and the time is 120min; in step five, a grinder is used for grinding, and the grinding is performed 3-5 times.
7. A prepreg, characterized in that, The invention comprises reinforcing fibers and a medium-temperature curing epoxy resin composition according to any one of claims 1-4, wherein the medium-temperature curing epoxy resin composition is impregnated in the reinforcing fibers.
8. The prepreg according to claim 7, characterized in that, The reinforcing fiber is carbon fiber; the fiber areal density of the prepreg is 133 g / m², and the resin content is 33 wt%.
9. A method for preparing a prepreg, characterized in that, Includes the following steps: The medium-temperature curing epoxy resin composition according to any one of claims 1-4 is made into a film; The prepreg is prepared by impregnating reinforcing fibers with the aforementioned adhesive film.
10. The method for preparing the prepreg according to claim 9, characterized in that, It also includes the following steps: The prepreg is laid to obtain a prepreg layup; The prepreg layup is placed in an autoclave, a pressure of 0.6-0.7 MPa is applied, and the temperature is raised to 125°C at a rate of 1-3°C / min. The temperature is maintained and cured for 2 hours, and then the temperature is lowered to below 60°C to obtain a composite material laminate.
Citation Information
Patent Citations
High-toughness epoxy prepreg and preparation method thereof
CN122145975A